2015
DOI: 10.4236/aces.2015.51007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Residual Stress on the Corrosion Behavior of Austenitic Stainless Steel

Abstract: In this paper we demonstrate that the residual stress introduced by several different surface finishes affects the critical current density for passivation and the passive current density in the anodic polarization curve of austenitic stainless steel and that those critical current densities can be reduced by controlling the residual stress by applying a cavitating jet to the backs of specimens. The results show that the current density either increased or decreased depending on the surface finish, and that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 29 publications
1
45
0
1
Order By: Relevance
“…Residual stress in the alloys can affect the corrosion properties including stress corrosion cracking and corrosion fatigue. Recently, it was reported that compressive residual stress may improve the intergranular corrosion resistance 19,30,31) . Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual stress in the alloys can affect the corrosion properties including stress corrosion cracking and corrosion fatigue. Recently, it was reported that compressive residual stress may improve the intergranular corrosion resistance 19,30,31) . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The nano-crystalline surface could increase the density of diffusion paths available for alloying elements to migrate and rapidly form a protective passive film 17,18) . In addition, residual stress in the surface layer affects the critical current density and the current density for passivation which are closely related to the formation and retention of the passivation layer 19) . The high mechanical energy imparted by UNSM to the steel surface may also induce the diffusion of the alloying elements 13,14,18) and therefore can affect the intergranular corrosion resistance of the stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…작은 Σ 경계 (이를 CSL(Coincidence Site Lattice 또는 special boundaries라 명명하고 있음))의 비율이 높을수록 특 성 개선이 이루어지는 것으로 보고되고 있다 [23][24][25][26][27][28][29][30][31][32][33] . 또한 입 계부식에 미치는 잔류응력의 영향에 대한 연구를 통하여 압축잔류응력이 존재하게 되면 부식을 억제시킬 수 있다고 보고하고 있으며 34) , 또한 최근의 결정립계 구조에 대한 연 구결과에 따르면 24) , 결정립계 현상(결정립계 확산 35) , 석출 36,37) , 부식 38,39) .…”
Section: 서론unclassified
“…The authors showed that the metallic dissolution was promoted by the presence of dislocation density and that the hydrostatic stress influenced the process of dissolution in the elastic range. Other authors have highlighted that residual stresses induced by surface finishing affected anodic polarization curve of an austenitic stainless steel . This paper demonstrated that compressive residual stresses decreased the passive current density and consequently enhanced the corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%